Nonverbal Codes in Online Intercultural EFL Classroom - Luthfiyyah Ainur Fitrizah; Syarifuddin Dollah (JPTK : JURNAL PENELITIAN TINDAKAN KELAS, 2026)
The rapid shift to online learning environments has transformed the nature of interaction in English as a Foreign Language (EFL) classrooms, particularly in intercultural contexts. While verbal communication has been widely examined, nonverbal communication in online intercultural EFL classrooms remains underexplored. This qualitative descriptive case study investigates the types and functions of nonverbal codes used in an online intercultural EFL classroom at the graduate level. Data were collected from recorded synchronous online class sessions involving culturally diverse students and analyzed using thematic analysis. The findings reveal that nonverbal communication was not diminished in the online setting but rather transformed into digitally mediated forms. The identified nonverbal codes include facial expressions, eye behavior, head and upper-body movements, paralinguistic features, and digital nonverbal cues such as mute–unmute behavior and response timing. These nonverbal codes functioned to express agreement and politeness, demonstrate respect and attentiveness, manage turn-taking, perform face-saving strategies, reflect culturally influenced communication norms, and compensate for the limitations of online interaction. The study highlights the importance of nonverbal awareness in fostering effective intercultural communication and intercultural communicative competence in online EFL classrooms.